2020
DOI: 10.1101/2020.11.05.370221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deletion ofCrtc1leads to hippocampal neuroenergetic impairments associated with depressive-like behavior

Abstract: Mood disorders (MD) are a major burden on society as their biology remains poorly understood, challenging both diagnosis and therapy. Among many observed biological dysfunctions, homeostatic dysregulation, such as metabolic syndrome (MeS), shows considerable comorbidity with MD. Recently, CREB-regulated transcription coactivator 1 (CRTC1), a regulator of brain metabolism, was proposed as a promising factor to understand this relationship. Searching for imaging biomarkers and associating them with pathophysiolo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 97 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…Increasing evidence suggests a close association between carbohydrate metabolism and depression, with abnormalities in carbohydrate metabolism being observed in the PFC (Baxter et al, 1989;Kennedy et al, 2001;Hennings et al, 2012;Li et al, 2015;Yao et al, 2023), HIP (Cherix et al, 2022), andHYP (Al-Massadi et al, 2021) of depression patients or depression-like animal models. This study found that quercetin may ameliorate depression-like behaviors in CUMS rats by modulating glycolysis/ gluconeogenesis and the pentose phosphate pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests a close association between carbohydrate metabolism and depression, with abnormalities in carbohydrate metabolism being observed in the PFC (Baxter et al, 1989;Kennedy et al, 2001;Hennings et al, 2012;Li et al, 2015;Yao et al, 2023), HIP (Cherix et al, 2022), andHYP (Al-Massadi et al, 2021) of depression patients or depression-like animal models. This study found that quercetin may ameliorate depression-like behaviors in CUMS rats by modulating glycolysis/ gluconeogenesis and the pentose phosphate pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of Crtc1 gene in mice induces insulin resistance and obesity, together with a depressive-like phenotype ( Altarejos et al, 2008 ; Breuillaud et al, 2009 , 2012 ; Rossetti et al, 2017 ). Using in vivo MRS at high field, we have observed that this phenotype translates into measurable neurochemical alterations in the hippocampus of Crtc1 –/– mice ( Cherix et al, 2020 ). Noteworthy, we identified lower levels of phosphocreatine relative to creatine, an indication that ATP production or consumption is impaired.…”
Section: Deregulation Of Brain Energy Homeostasis In Major Depressive...mentioning
confidence: 99%